MUSEO ETNOGRAFICO MONTUBIO Y LA PRESERVACION DE LA HERENCIA CULTURAL DE LA PROVINCIA DE LOS RIOS - CHIMBO MULLO NATHALY DE LAS MERCEDES (2024)
The objective of this research is to evaluate the community's perception of the need and viability of creating a Montubio Ethnographic Museum in the province of Los Ríos in order to preserve and promote the rich cultural heritage of the Montubio community. The study uses a quantitative approach, using a non-experimental and exploratory design, to collect the necessary data, through the application of surveys to a sample of 384 residents of the province of Los Ríos. The objective of the surveys is to identify the cultural characteristics of the Montubia community and evaluate the interest of the inhabitants in the preservation of their cultural heritage through a museum. The creation of a Montubio ethnographic museum in Los Ríos is a viable and beneficial proposal for the Rios community. This project has the potential to strengthen the Montubio cultural identity, also ensure the transmission of its legacy to future generations, promote cultural development and educational in the province. The museum is conceived as a space dedicated to documenting, conserving and exhibiting key elements of local culture, such as agricultural practices, the Montubio rodeo and ancestral archaeological remains. The implementation of this project would promote cultural tourism in the Province, generating a positive impact on the local economy, promoting cultural and educational development in the region.